2020
DOI: 10.1101/2020.11.13.20231555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing services for long Covid: lessons from a study of wounded healers

Abstract: Persistent symptoms lasting longer than 3 weeks are thought to affect 10-20% of patients following Covid 19 infection. No formal guidelines exist in the United Kingdom for treating ‘long Covid’ patients and services are sporadic and variable, although additional funding is promised for their development.In this study narrative interviews and focus groups are used to explore the lived experience of 43 healthcare professionals with long Covid. These individuals see the healthcare system from both professional an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 12 publications
(17 reference statements)
3
40
0
2
Order By: Relevance
“…It would appear that long COVID has so far avoided the earlier obscure fate of ME/CFS, with an outpouring of public and expert acknowledgement for its status as a medical illness and its significant long-term health impact [ 79 , 80 , 81 , 82 ]. Many have attested to the importance of providing patient support and monitoring patients’ chronic symptoms post-COVID, as well as the need for further research into long COVID [ 83 , 84 , 85 ]. Though there is no established treatment protocol for patients with long COVID symptoms, many have acknowledged and suggested the need and benefits of rehabilitation [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would appear that long COVID has so far avoided the earlier obscure fate of ME/CFS, with an outpouring of public and expert acknowledgement for its status as a medical illness and its significant long-term health impact [ 79 , 80 , 81 , 82 ]. Many have attested to the importance of providing patient support and monitoring patients’ chronic symptoms post-COVID, as well as the need for further research into long COVID [ 83 , 84 , 85 ]. Though there is no established treatment protocol for patients with long COVID symptoms, many have acknowledged and suggested the need and benefits of rehabilitation [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, building hope and resilience, social connection, and peer supports are essential in managing psychological issues (136). In a qualitative study on 43 health professionals, Ladds et al (23) reported that the participants repeatedly mentioned the role of social media in feeling better and diminishing their anxiety/stress and stigma when communicating with others and with their colleagues about their symptoms.…”
Section: -A) General Carementioning
confidence: 99%
“…More than 80 dedicated Post-COVID assessment clinics have been announced in England (17), but many centres only started accepting referrals one year after the first pandemic wave. Various care models have been proposed through expert and patient consensus (18)(19), but real world data are lacking, particularly in community settings, where the majority of COVID-19 and Long COVID patients are managed.…”
Section: Introductionmentioning
confidence: 99%